Ethical commitment and citizenship - Estrada-Pérez, Luis F. (2021)
The present work is composed of three parts. The first is dedicated to presenting an approach to the distinction between ethics and morals. The second part works on the importance of concepts such as "moral basis", "search for value" and "moral sensitivity" developed by Nozick (1981). The third section presents the relevance of the ethical commitment to the exercise of citizenship based on Nozick's approaches to the “ethical push” and in the search to make our life meaningful. The main hypothesis of this study is that there is a continuity between ethical motivation, ethical commitment and the democratic exercise of citizenship.